GE_GERICHTE P/18116/2010 vom 28. Juni 2019 - GE Cour de justice (2019)
CLASSEMENT DE LA PROCÉDURE;IMPUTATION;FRAIS DE LA PROCÉDURE;INDEMNITÉ(EN GÉNÉRAL);FAUTE | CPP.319; CPP.426.al2; CPP.430; CP.138; CP.158; CP.165